2017
DOI: 10.7567/jjap.56.0802b4
|View full text |Cite
|
Sign up to set email alerts
|

Soft errors in 10-nm-scale magnetic tunnel junctions exposed to high-energy heavy-ion radiation

Abstract: The influences of various types of high-energy heavy-ion radiation on 10-nm-scale CoFeB–MgO magnetic tunnel junctions with a perpendicular easy axis have been investigated. In addition to possible latent damage, which has already been pointed out in previous studies, high-energy heavy-ion bombardments demonstrated that the magnetic tunnel junctions may exhibit clear flips between their high- and low-resistance states designed for a digital bit 1 or 0. It was also demonstrated that flipped magnetic tunnel junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…When radiation-induced errors do occur, it most often a result of interaction with the select device or supporting CMOS peripheral circuitry. However, there are some reports of device-level SBUs in highly scaled STT-MRAM bits (MTJs) [92] and PCRAM bits [139] which merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When radiation-induced errors do occur, it most often a result of interaction with the select device or supporting CMOS peripheral circuitry. However, there are some reports of device-level SBUs in highly scaled STT-MRAM bits (MTJs) [92] and PCRAM bits [139] which merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Damage and bit upsets induced by heavy ions were studied by Kobayashi et al [91], specifically investigating the effect of 15-MeV silicon atoms on the CoFeB/MgO/CoFeB pMTJ devices with a diameter of 70 nm and did not find resistance change. Later, the same group found that singleevent bit flips can occur in an MTJ cell resulting from heavyion exposure, depending on both the LET and properties of the bit [92]. In this second study, MgO/CoFeB pMTJ with diameters between 40 and 80 nm were subject to heavy-ion bombardment.…”
Section: A Stt Magnetic Memorymentioning
confidence: 92%
See 1 more Smart Citation
“…That hardness makes MRAM promising for applications in extreme environments 1 . Still, magnetic tunnel junctions (MTJs) are not tolerant to all sorts of radiation [2][3][4] : indeed, ion-irradiation-induced modifications of MTJs have been observed, extending from soft errors (undesired but recoverable magnetization switching, provoked by localized heating 4 ) to permanent changes in magnetic and electrical properties produced by structural modifications. The degree of such modifications is governed by the theelastic an inelastic energy losses in the materials, which are dependent on the ion mass and charge state, kinetic energy, fluence, target composition; also the chemical bonding in the target and the temperature of the latter are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Even if MTJ has high tolerance to radiation [45], the MOS access transistors in MTJ-based memory structures may be impacted by radiation. Among other factors, tolerance to radiation is one important and studied field [46][47][48][49] when it is necessary to take into account performance and risks of MRAM in the integration process of MOS technology.…”
mentioning
confidence: 99%